Technology assessment of Bahalina ageing process - Lagdamen, Emmanuel E. (University of the Philippines Diliman, 2014)
This special paper has been made with an aspiration to infuse technology to a less intervened product named 'bahalina'. It is 'aged coconut toddy' that involves tedious procedure and long period of time waiting the entire process to insure potency and excellent quality. Bahalina has been widely known as coconut red wine, and it captures the interest of health conscious individuals considering its published proven benefits. Consequently, it captures not only the local folks, but also at the national and international market. However the supply is quite limited considering its process that requires long period of time to insure quality. In that sense, the bahalina procedures could only cater the local customers of Leyte and perhaps nearby provinces. Other provinces are also producing 'tuba' but they can never claim the distinct sensory tasts of bahalina as could be attested by red wine drinkers and enthusiasts. Bahalina has form part in the culture and tradition of the Leyteños and already known as its trademark. However, one of the technology constraints is on how to accelerate the entire process purposely for mass production without relying on the conventional way of producing the said product. Acceleration of the entire process is the solution but the usual potency and quality must not be compromised. The demand of the said product is increasing and it is high time to look for possible technology solution. The framework of the study is a unique mixed hybrid strategy framework. The initial approach is explorative research through analysis of applicable literatures, researches conducted, and conducting possible interviews with wine experts, tuba-bahalina processors from small scale to establish firms. All possible avenues shall be explored to gather data and information to be consolidated as the basis for possible technology solution. The said information could be the basis for future research on bahalina manufacturing standard that will accelerate and or reduce the entire process. The very purpose is to improve efficiency and increase bahalina production taking into consideration the usual excellent quality. There were published researches and related literatures all over in relation with tropical wines specifically on 'tuba'. However, based on my on-line researches, data gathering and interviews, no one focusing on manufacturing standardization of bahalina more importantly to accelerate and or reduce its entire process without compromising the usual quality. The researcher learned thru one of the wine experts that most of researches were not tested and shall be validated. Therefore, unless particular research has been tested and technically proven, it shall not be diffused to possible adopters and be made as standard. The study specifically shall be focusing on their manufacturing operations and best practices that possibly accelerate for instance fermentation, and or reduce the entire process in bahalina production as to compare to conventional way without compromising the desired acceptable quality. The ultimate objective is to investigate their respective unique processes, technology used, and best practices to establish the most reduce processing in order to cater the increasing demand of the product in the local and international market. The researcher believed that 'bahalina' is one of the promising industries in Leyte that needs technology intervention. The initial steps are through research exploration and exhaust the possibilities in finding the right technology and or information which could be diffused to bahalina processors and or could be used by future researcher and appropriate agencies to establish possible standard process and formulation that will reduce the entire manufacturing process with the standard quality. However, it turn out that up to this point there is no available manufacturing standard and or technology that will enhance and reduce the process and therefore most of the bahalina producers still practicing the conventional way. Although, there are published researches that have been reported attempting to explain for instance, the significant effect of the kind of yeast and additives that will enhance and improve the process. Finally, the researcher has decided to identify and focus on two most established bahalina manufacturing firms known of its product quality and tested processes for a period of time and its dynamic operations namely DGCRATER, Incorporated also known as Vino de Coco, and EF Winery, located in Marasbaras, Tacloban City, and Palo, Leyte, respectively. The researcher has presumed that the said firms have internally developed unique processing techniques and or technology aside from their respective best practices. The result and findings of the assessment and audit shall be consolidated and analyzed which could be the basis and or take off point for future researches with an aim to establish bahalina manufacturing standard that will accelerate the ageing process and or reduce the entire bahalina production from 2-5 years to 6 months to 1 year.